Oxygen reduction reaction on anisotropic silver nanoparticles in alkaline media - Gupta R.K.; Verma A.D.; Sinha I.; Malviya M. (My University, 2025)
The effect of anisotropy of Ag nanoparticles on their electrocatalytic activity was investigated. By using increasing amounts of Cu salt etchant, we could obtain two AgNPs samples (S1 and S2) with different percentages of anisotropic nanoparticles. The third AgNPs sample was synthesized in the absence of any etchant and therefore resulted in the formation of only spherical nanoparticles. Investigation of ORR activity in an alkaline solution of these AgNPs samples showed that the S1/GC electrode gives rise to better reduction peak current, more positive reduction peak potential and stable electrocatalytic performance. Better results for the S1/GC electrode as compared to S2/GC electrode & S3/GC electrode can be owed to a higher percentage of anisotropic nanoparticles in S1 sample. © 2017